Advancements in digital transformation among Malaysian zakat institutions - Che Mohd Salleh, Marhanum; Rosli Amran, Aqil Alexander; Mohd Sofian, Fatimah Noor Rashidah (Department of Awqaf, Zakat and Hajj, 2025)
The integration of advanced technology into the management of zakat is significantly transforming the way institutions operate, collect, and effectively distribute zakat funds to those in need. The level of technology adoption among zakat institutions in Malaysia remains varied, with some institutions being more advanced while others still lag behind. This research therefore aims to evaluate the current state of technology usage among Malaysian Zakat Institutions as of 2025. In detail, this research focusing on the institutions’ website technology disclosures, enactment updated, online applications and compares the 14 zakat institutions, highlighting trends, gaps, and best practices in technological transformation. This comprehensive study employs a qualitative, comparative research design methodology to thoroughly analyze the current state of technology adoption across the 14 prominent zakat institutions in Malaysia. The analysis reveals several critical conclusions regarding the evolution of zakat institutions in the digital landscape. Firstly, there has been a universal adoption of online payment systems across all zakat institutions, signifying a broader national transition toward digital transactions that enhance convenience and accessibility for contributors. However, disparities in technological advancement persist, as larger institutions typically lead in digital innovation, whereas smaller organizations struggle with limited resources and expertise, resulting in a fragmented technological landscape. This research significantly contributes to the field by providing an up-to-date, comparative analysis of technology adoption across Malaysian Zakat Institutions, highlighting progress, disparities, and best practices, and offering insights to inform policy and strategic improvements in digital zakat management.